COVID-19 is exacerbating inequalities in food security - Swinnen, Johan (International Food Policy Research Institute, 2020)
COVID-19 is disrupting economies and food systems everywhere, but the poor will suffer the greatest risk of food crisis. Based on model predictions, early empirical evidence, and lessons from previous crises, it is clear that the risk of increased food insecurity depends on the level of economic development. As employment and income opportunities fall for the poor, the gap between rich and poor is growing. Among the poor, urban poor and women are especially vulnerable.